DOI: 10.31274/rtd-180813-15513
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity on Avena and growth response of Pseudomonas coronafaciens (Elliott) Stapp

Abstract: The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleed-through, substandard margins, and improper alignment can adversely affect reproduction. In the unlikely event that the author did not send a complete manuscript and there are missing pages, these will be noted. Also, if unauthorized copyright material had to be removed, a note will indicate the deletion. UMI UMI Microform DP13322

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Glasshouse and laboratory tests revealed that poor establishment in the field was due to the high rate of mortality amongst infected seedlings, a large proportion of which died at the first-leaf stage before appearing above ground, a feature also observed and reported by Kingsolver (1944).…”
Section: Trialssupporting
confidence: 64%
See 2 more Smart Citations
“…Glasshouse and laboratory tests revealed that poor establishment in the field was due to the high rate of mortality amongst infected seedlings, a large proportion of which died at the first-leaf stage before appearing above ground, a feature also observed and reported by Kingsolver (1944).…”
Section: Trialssupporting
confidence: 64%
“…More recently Kingsolver (1944) has reported sources of field resistance. The varieties Anthony, Boone, Marion, Bannock, Gopher, Landhafer and Mutica Ukrainica, together with selections from crosses of these parents, were found to be, in general, wholly susceptible.…”
Section: Varietal Reaction To Halo Blightmentioning
confidence: 99%
See 1 more Smart Citation
“…A bacterial causal agent of a disease of bromegrass (Reddy and Godkin, 1923) probably is also P. syringae pv. coronafaciens , because isolates from bromegrass were able to cause disease on oats (Reddy and Godkin, 1923; Kingsolver, 1944). In addition, bacteria that cause a disease of corn called ‘chocolate spot’ were originally classified as ‘ P. coronafaciens pv.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, plant breeding offers an even cheaper and equally efficient means of control, especially as good resistance has been found in various hexaploid varieties and species (Caldwell. Mulvey and Compton, 1946;GriflRths and Peregrine, 1960;Kingsolver, 1944). Because of the possibility of combining the factors for resistance with desirable agronomic characters into one improved variety by hybridization, a knowledge of the mode of inheritance of resistance to halo blight is of great importance to the breeder.…”
mentioning
confidence: 99%